World encyclopedia of police forces and correctional systems - Kurian, George Thomas; Kurian, George Thomas (Gale virtual reference library, 2006)
This fully updated version of the original 1989 edition of the World Encyclopedia of Police Forces and Correctional Systems describes the national law enforcement and correctional systems of more than 195 countries across the globe.